The Impact of FinTech on Financial Institution Performance and Risk: An Empirical Analysis from China - Wenna Wang; Deping Xiong; Yabin Li (SAGE Open)
This study conducted in-depth analysis using a random effects panel data analysis method, utilizing a comprehensive dataset of financial companies listed on the Shanghai and Shenzhen stock exchanges from 2001 to 2022 to investigate the impact of financial technology on the performance and risk of Chinese financial institutions. Based on data from financial companies listed on the Shanghai and Shenzhen stock exchanges between 2001 and 2022, the study found that while financial technology had no significant effect on return on assets (ROA), it significantly improved the liquidity ratio (LR). This finding suggests that although the advantages of financial technology in enhancing operational efficiency and risk management do not directly translate into immediate profitability, they do lead to significant improvements in liquidity management. The study underscores the crucial role of financial technology in the evolution of the financial sector and emphasizes the necessity of establishing a balanced regulatory framework, enhancing education, and promoting deep integration between financial technology and traditional financial services. Through robustness checks, this study ensures the reliability of its findings.